Aging improves tenderness of longissimus muscle steaks from fed mature cows - Gipe, A.N.; Marston, T.T.; Higgins, James J.; Hutchinson, Stacy L.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Steaks from cows are tougher than those from young steers and heifers. This difference is often attributed to the increased cross-linkage of collagen in muscle of mature animals that is considered very stable and more resistant to postmortem degradation. Aging steaks from young steers and heifers is a common postmortem practice used to improve tenderness of steaks from the ribeye roll and strip loin. Improvement in tenderness because of aging has been attributed to enzymatic degradation of, primarily, the myofibrillar fraction of muscle and is most beneficial for low connective tissue muscles. Because muscles from mature cows have more collagen cross-linking, postmortem tenderization methods, such as blade tenderization and enzymatic tenderization, are often used to increase tenderness of steaks from mature cows. However, few studies have investigated the effect of aging on tenderness of longissimus muscle steaks from fed mature cows. Therefore, the objective of this study was to determine effects of aging on tenderness of longissimus steaks of fed mature cows from different management strategies.
Keywords: Beef; Cattle; Tenderness; Longissimus